'You come as a human being…': exploring sense of equality in arts interventions through an ethnographic study of Shared Reading - Kristensen, Mette Marie; Rod, Morten Hulvej; Simonsen, Peter; Folker, Anna Paldam (Medical humanities, 2025)
Research shows that the arts hold a particular potential for promoting health, well-being and social inclusion for vulnerable people. However, the use and consumption of the arts tend to be socially skewed in favour of people with high cultural, social and economic capital. While extensive research has been conducted on how to create equal access to arts activities for vulnerable groups, little research has investigated how to ensure meaningful engagement with the arts by this group. Shared Reading (SR) has had considerable success in engaging vulnerable groups in collective literary practices, and research suggests that this may partly be due to the unique forms of social and literary engagement that the concept fosters. These forms of engagement, we suggest, lay the foundation for a sense of equality among participants that may promote social connectedness and well-being. On this basis, the present study aims to investigate whether and how a sense of equality may play a role in SR practices. The study found that SR promotes a sense of equality by creating a space where social interaction and relatedness does not hinge on social roles, but rather on lived experiences-and vulnerabilities inherent to these-conveyed through literary texts and shared among participants. However, to promote a sense of equality in SR, meaningful engagement for all participants must be ensured, making facilitation an essential element of SR practices and an important focus in arts interventions in general. We conclude that SR, and arts interventions more generally, may be a promising way to promote a sense of equality, but further research is needed on the specific qualities of and potential contexts for the promotion of a sense of equality.